A Meta-Analytic Review of Hypodescent Patterns in Categorizing Multiracial and Racially Ambiguous Targets. (May 2021) - Young, Danielle M.; Sanchez, Diana T.; Pauker, Kristin; Gaither, Sarah E.
Research addressing the increasing multiracial population (i.e., identifying with two or more races) is rapidly expanding. This meta-analysis ( k = 55) examines categorization patterns consistent with hypodescent, or the tendency to categorize multiracial targets as their lower status racial group. Subgroup analyses suggest that operationalization of multiracial (e.g., presenting photos of racially ambiguous faces, or ancestry information sans picture), target gender, and categorization measurement (e.g., selecting from binary choices: Black or White; or multiple categorization options: Black, White, or multiracial) moderated categorization patterns. Operationalizing multiracial as ancestry, male targets, and measuring categorization with binary or multiple Likert-type scale outcomes supported hypodescent. However, categorizing multiracial targets as not their lower status racial group occurred for female targets or multiple categorization options. Evidence was mixed on whether perceiver and target race were related to categorization patterns. These results point to future directions for understanding categorization processes and multiracial perception.